Bipolar Organic Polymer for High Performance Symmetric Aqueous Proton Battery. Issue 8 (26th June 2021) - Sun, Tianjiang; Du, Haihui; Zheng, Shibing; Shi, Jinqiang; Yuan, Xuming; Li, Lin; Tao, Zhanliang
Abstract: Bipolar electroactive organic molecules receive an increasing research attention as electrode materials for rechargeable batteries due to their flexibility, controllability, and environmental friendliness. While its application for symmetric aqueous proton batteries is still in its infancy. Herein, a symmetric aqueous proton battery (APB) based on a bipolar poly(aminoanthraquinone) (PNAQ) is developed. The conductivity and solubility of PNAQ are significantly improved by introducing a polyaniline‐like skeleton. It is demonstrated that the quinone‐based moieties allow H + reversible uptake/removal and the benzene ring‐based units achieve HSO4 – adsorption/desorption. The fabricated symmetric APB exhibits a high discharge capacity of 85.3 mA h g –1 at 5 C and excellent rate performance (77 mA h g –1 at 100 C). The good rate performance benefits from capacitance‐like ions diffusion mechanism. Furthermore, surprisingly, the system can also operate at −70 °C and shows superior electrochemical performance (60.4 mA h g –1 at −70 °C). Abstract : A symmetric aqueous proton battery (APB) based on a bipolar poly(aminoanthraquinone) (PNAQ) is developed. The conductivity and solubility of PNAQ are significantly improved by introducing a polyaniline‐like skeleton. The symmetric APB can operate well at low temperatures from +25 to −70 °C. A high discharge capacity of 60.4 mA h g –1 is obtained at −70 °C.